Environment Friendly Practices of Congress Hotels: Examples from Antalya Region of Turkey - AKSU, AKIN; DEMİR, AYŞEGÜL and ÖZ, KADİR and ARIHAN, MEHMET UĞUR (Turizam, 2018)
Beside the economic effects of tourism, possible negative environmental effects should be taken in consideration. Generally, tourism activities affect natural areas, the flora and fauna of nature. To prevent negative effects of tourism development and protect nature both governments, and non-governmental organizations, are trying to force some measures on tourist establishments. It seems, behaviors of human and interest of public will solve nature-related problems in the future. In hospitality related literature, it is possible to find out different researches showing environment friendly practices, products and effects of tourism. In this study, national congress participants’ evaluations about their hotels’ environment friendly practices were examined so as to draw attention importance of environment friendly practices for tourism. Suitable to the latest trends, national congress participants in the sampled hotels are sensitive to environmental friendly practices in general. It can be said that there is a positive and meaningful relationship between environmentally friendly practices and the intention to purchase.